Re-envisioning the scholarship of engagement: Lessons from a university-school partnership project for mathematics and science teaching - Ndlovu, MC (South African Journal of Higher Education, 2011)
The purpose of this article is to report on a formative evaluation research study of a university-school partnership for mathematics and science education within a community engagement and social justice perspective in higher education in order to inform redesign and replicability. The partnership involved the school-based systemic intervention through teacher professional development in which university-based facilitators embarked on class visits with the aim of identifying teacher needs, co-teaching and offering professional support over a four-year period. This was in contrast to traditional inspection visits which teachers and teacher unions are not comfortable with. Five historically disadvantaged secondary schools and their ten feeder primary schools were involved in this study with a view of providing equal opportunities to learners from marginalized communities in the Stellenbosch region of the Western Cape. That the schools were located in socio-economically disadvantaged communities added a social justice perspective to the partnership goals. Initial results of the study suggest that an intervention programme that is collaborative and responsive to local needs can achieve greater impact if sufficiently funded and efficiently facilitated. Teachers can open up to the change initiative and build self-reflective professional communities of practice that enrich their practice and ultimately impact positively on learner achievement in the gateway subjects of mathematics and science.